An Experimental Study of the Influence of Hand-Arm Posture and Grip Force on the Mechanical Impedance of Hand-Arm System. (10th June 2021) - Zhang, Wenjie; Wang, Qichao; Xu, Zheng; Xu, Hongmei; Li, Hang; Dong, Jiajun; Ma, Xinbo
Abstract : In order to investigate the effects of hand-arm posture, grip force, push force, and vibration excitation intensity on the mechanical impedance of human hand-arm system, a test system with a self-developed vibration handle has been prepared. Based on the testing system, the mechanical impedance of the hand-arm system of seven Chinese adult males were tested and calculated under the random vibration excitation with the frequency of 10–1000 Hz. The results reveal that when the frequency is lower (<40 Hz), the hand-arm system with an elbow angle of 180 o produces a higher mechanical impedance; when the frequency ranges from 40 Hz to 100 Hz, the hand-arm system with an elbow angle of 90 o generates a higher mechanical impedance; while when the frequency is higher (>100 Hz), the hand-arm posture seems to have no obvious effect on the mechanical impedance. Higher grip or push force would increase the frequency corresponding to the peak value of the mechanical impedance and often correspond to a higher mechanical impedance in a specific frequency range (30–200 Hz). When the frequency is lower (<140 Hz), vibration intensity has certain effects on the mechanical impedance of the hand-arm system. In conclusion, vibration intensity does not directly affect the mechanical impedance, but an increase in grip or push force often causes an increase in mechanical impedance and a higher frequency that corresponds to the peak of mechanical impedance.